2023
DOI: 10.1002/ppap.202300067
|View full text |Cite
|
Sign up to set email alerts
|

The applications of cold atmospheric plasma in dentistry

Abstract: Cold atmospheric plasma (CAP), as a noninvasive technology, has shown promise in dentistry as it might successfully treat various oral conditions. The antimicrobial capacity of CAP has been proven and it is effective in reducing the main microorganisms responsible for oral infections. Furthermore, CAP has also been explored in the field of tissue regeneration with a great response from both soft and hard tissue. The surface modification ability of CAP is another area of interest, revealing a potential improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 128 publications
0
3
0
Order By: Relevance
“…UV light-induced superhydrophilicity of titanium dioxide was first described by Wang et al in 1997 [18]. Clinicians also investigated the effect of plasma treatment of Ti surfaces for accelerated cell adhesion, in regard to organic and inorganic surface contaminant removal [17,23,[39][40][41]. In a systematic review by Pesce et al, the treatment of Ti dental implant surfaces using plasma or even UV was described as an effective method for improving the osseointegration process [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UV light-induced superhydrophilicity of titanium dioxide was first described by Wang et al in 1997 [18]. Clinicians also investigated the effect of plasma treatment of Ti surfaces for accelerated cell adhesion, in regard to organic and inorganic surface contaminant removal [17,23,[39][40][41]. In a systematic review by Pesce et al, the treatment of Ti dental implant surfaces using plasma or even UV was described as an effective method for improving the osseointegration process [42].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma treatment consists of ionized gas (air, oxygen, argon, or nitrogen) in a vacuum chamber that forms plasma and removes contaminants from pure titanium metal surfaces and increases hydrophilicity, and it has been used for that purpose for several decades and has been shown to increase cellular adhesion to polymeric materials [21]. Numerous studies reported the advantages of implant plasma treatment, such as significantly higher in vitro fibroblast adhesion and proliferation compared to non-treated surfaces [17,22] and increased cytokine and growth factor secretion, resulting in improved wound healing [23]. However, a large majority of available studies in that area have described in vitro results and very few have tested surface treatment in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…This review aims to outline the current clinical use of plasma medicine and the cell signalling pathways responsible for eliciting cell responses to CP therapy in both activating cells, as seen in wound healing, and destruction of cancerous cells from in vitro, ex vivo, and in vivo studies. Although the antimicrobial effect of CP is well established and is an important part of wound care, this activity is independent of mammalian cell responses and is not discussed here, but has been covered by several other fantastic reviews [25][26][27]. Finally, gaps in future research and the limitations of plasma medicine are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment process is highly efficient, environmentally friendly, low cost, short time-consuming, and easily industrialized (Gururani et al, 2021). Plasma technology has been widely used in the fields of medicine (Bernhardt et al, 2019;Gümbel et al, 2017;Silva et al, 2023), food processing (Coutinho et al, 2018), and material surface modification (Bulbul et al, 2019;Zhang et al, 2018). In recent years, researchers have carried out studies on the effects of cold plasma on plant growth and the extraction of compounds (Amorim et al, 2023;Kumar et al, 2023;Li et al, 2019;Li et al, 2023;Pan et al, 2021;Zahoranová et al, 2018).…”
Section: Introductionmentioning
confidence: 99%